Pemberdayaan Masyarakat Miskin melalui Program Kelompok Usaha Bersama (Kube) (Studi Deskriptif tentang Usaha Ekonomi Produktif (UEP) di Kelurahan Menanggal Kecamatan Gayungan) - Tukiman - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research utilize diskriptif kualitatif’s method that analyzes a variable which is indigent society empowerment via programs effort group with a study diskriptif about productive economy effort at Menanggal-Gayungan’s district. Economic effort help management productive (UEP) collegial and individual, pengguliran passes through to lent fund social solidarity fee (IKS), and UEP’S profit sharing in agglomerate effort with. Result of this research is that on duty Province Social and on duty city Social via UPKM has done masyrakat’s empowerment hole in the wall via effort group with deep shaped productive economic effort, help is done / is given collegial / agglomerate but its seed money is brought off on an individual basis but regular in kelompok.dan’s responsibility in that management available agglomerate liabilities that shall be done which is pengguliran pass through social solidarity fee that at moves over every month up to 1 year, pengguliran is done to band together KUBE new that help that is given gets merata. In pengguliran this there are many member that don’t order in does pengguliran in this help management no profit sharing in agglomerate because of seed money which get on an individual basis been brought off. With this empowerment really helps they to fix family economics.Keywords: Management in Productive Economic Effort (UEP) and Economic effort help management productive (UEP)